Political Mediatization in the Digital Era: The Case of WALHI West Sumatera’s Environmental Advocacy - Arifuddin, Muhammad Thaufan; Arif, Ernita; Darwis, Yuliandre; Rinaldi, Rinaldi; Dalmenda, Muhammad Al-Amin (UI Scholars Hub, 2026)
This article examines how political mediatization operates at the local level through environmental civil society activism in post-authoritarian Indonesia. Focusing on the West Sumatra chapter of the Indonesia Forum for Environment (WALHI) as a critical case, the study argues that media logic is not merely imposed by political elites or mainstream media, but is strategically appropriated by local civil society organizations to contest oligarchic power, shape public agendas, and sustain democratic engagement at the subnational level. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews with environmental activists and youth organizers, and an analysis of organizational documents, digital platforms, and media coverage. The findings show that WALHI West Sumatra integrates digital media into its core advocacy practices, allowing localized environmental and agrarian conflicts to gain public visibility and political resonance. Political mediatization at the local level takes a hybrid form, combining offline grassroots mobilization and legal advocacy with online campaigning, narrative framing, and networked alliance-building. Youth collaboration emerges as a key mediating mechanism that expands advocacy frames and amplifies issue visibility across digital public spheres. Despite structural constraints such as limited resources and oligarchic governance, mediatized activism remains an important source of strategic agency. This study contributes to political mediatization scholarship by situating it within the context of local environmental activism in post-authoritarian Indonesia.